Poverty Reduction For Coastal Communities In Indonesia Through Community Empowerment Training - Teguh Prasetyo; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno; Budiman Djoko Said (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Coastal communities in most parts of Indonesia are one of the poorest community groups.Coastal villages where the majority of the population earn a living as fishermen, fish farmers, or water cultivators, fishing culture has a major influence on the formation of the cultural identity of coastal communities as a whole. Efforts to reduce poverty in Indonesian society, especially in coastal areas, are carried out with a community empowerment education and training approach through government programs that provide skills training which will later be useful for a new job outside of being a fisherman. This type of research is descriptive qualitative. This study aims to address poverty alleviation in coastal communities according to the characteristics and needs of the community. It is hoped that the community can be creative and innovative in finding jobs outside of their work as fishermen and the like.